The relationship between peripheral muscle strength and respiratory function and respiratory muscle strength in athletes - Akinoglu, B.; Kocahan, T.; Özkan, T. (Journal of Exercise Rehabilitation, 2019)
The aim of this study is to determine the relationship between peripheral muscle strength, respiratory function and respiratory muscle strength in athletes. The study included a total of 150 elite athletes (judo, rowing, gymnastics) (age, 16.94±2.37 years; length, 167.70±12.23 cm; body weight, 62.87±17.33 kg; body mass index, 21.95±2.92 kg/m2). Isomed 2000 isokinetic dynamometer was used to assess peripheral muscle strength. The strength of the dominant side knee flexor and extensor muscles was evaluated at 60°/sec and 180°/sec. At the end of the evaluation; knee flexion and extension peak torque (PT) values and flexion and extension PT values rates were obtained at 60°/sec and 180°/sec. Respiratory function and respiratory muscle strength of the athletes were evaluated using a digital spirometer. To assess respiratory function, forced vital capacity maneuver and maximal minute ventilation test; to assess the strength of the respiratory muscles, maximum inspiratory pressure and maximal expiratory pressure tests were performed. There was a strong relationship between muscle strength of knee flex-or and extensor muscles and respiratory function (r=-0.268/0.813, P<0.05). There was a strong moderate correlation between knee flexor and extensor muscle strength and all parameters of respiratory muscle strength (r=0.206/0.411, P<0.05). The knee flexor and extensor muscle strength, respiratory function and respiratory muscle strength develops parallel to each other and the codevelopment of these parameters together with special exercises to increase respiratory muscle strength will improve the performance of the athletes.